The Napoleon complex revisited: New evidence from professional soccer - Giulio Callegaro; Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2024)
We analyse evaluation biases caused by physical attributes. Using data from German elite soccer, we find that referees are more inclined to sanction players when the difference in body size is sufficiently large. Moreover, we document an 'inverse Napoleon effect' in situations when the referee is confronted with smaller players, suggesting that sanctions are used as a substitute for authority gained by stature in the industry. Further analyses reveal that referees discriminate less against more talented players and teams with a higher concentration of these players. Finally, we find that the bias is reduced but still exists for the group of more experienced referees.
Keywords: J71; L83; Z20; 330; evaluation; discrimination; social dominance; referee bias; soccer